2004
DOI: 10.1080/14622200310001656957
|View full text |Cite
|
Sign up to set email alerts
|

Psychopharmacological interactions between nicotine and ethanol

Abstract: Epidemiological, clinical, and laboratory evidence has shown a positive correlation between cigarette smoking and ethanol use, and previous studies suggest some commonality in the neural pathways mediating effects of nicotine and ethanol. In this study, the subjective and behavioral interactions among nicotine, ethanol, and the nicotinic antagonist mecamylamine were investigated. The main objectives were to determine how the rewarding effects of nicotine might be modified by ethanol, and to compare the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
139
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(151 citation statements)
references
References 0 publications
9
139
1
2
Order By: Relevance
“…In contrast to our results, Rose et al (2004) did not demonstrate any effect of alcohol on the number of cigarettes smoked. It is possible that the inclusion of a 'smoking tab' in the current study helped to elucidate the effect of alcohol on tobacco use by providing an incentive to resist smoking.…”
Section: Discussioncontrasting
confidence: 57%
“…In contrast to our results, Rose et al (2004) did not demonstrate any effect of alcohol on the number of cigarettes smoked. It is possible that the inclusion of a 'smoking tab' in the current study helped to elucidate the effect of alcohol on tobacco use by providing an incentive to resist smoking.…”
Section: Discussioncontrasting
confidence: 57%
“…Also, given that alcohol appears to enhance the rewarding effects of nicotine (Glautier et al, 1996;Rose et al, 2002Rose et al, , 2004) and nicotine appears to enhance the rewarding effects of alcohol (Kouri et al, 2004;Perkins et al, 1995), the association between increasing levels of tobacco and alcohol use may reflect bidirectional influences in which the use of one substance makes use of the other substance more rewarding and therefore more likely to progress to greater use. Prior longitudinal research with adolescents and young adults has found that greater alcohol use prospectively predicts greater tobacco use and vice versa (Jackson et al, 2002).…”
Section: Progression To Daily Smoking and Dependencementioning
confidence: 99%
“…Alcohol use can potentiate the rewarding effects of smoking (Glautier et al, 1996;Rose et al, 2002Rose et al, , 2004, which could increase motivation to smoke. Thus, greater levels of alcohol involvement may be associated with a consistent linear increase in the odds of progressing to daily smoking.…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible that when smokers stop, this is part of a broader attempt to reduce their health risks that would include a reduction in alcohol consumption as well 28, 29, 30. A third possibility is that not smoking makes it easier to reduce alcohol consumption or vice versa, because each provides a cue for the other or because of pharmacological interactions between nicotine and alcohol 31, 32.…”
Section: Introductionmentioning
confidence: 99%